The Digital Transformation of the Educational Environment - the Main Effect of the Change Caused by the SARS-CoV-2 Pandemic - Georgiana – Tatiana Bondac; Nicoleta Aura Dragnea Alecsandrescu (Risk in Contemporary Economy)
Digital transformation has changed the economy and society, having an ever-increasing impact on everyday life. However, before the COVID-19 pandemic, its impact on education and training was much more limited. Education providers around the world have rushed to adopt smart technologies to ensure continuity of education for all, adapting to online teaching and learning with new, agile and more efficient solutions. The pandemic has shown that it is essential to have an education and training system ready for the digital age. This article aims to answer the question "Is the digitalization of the educational environment advantageous for the teaching-learning process?"